GAMBARAN SIKAP BELAJAR POSITIF SISWA KELAS VIII DI SMPN 3 BATUJAJAR - Mufridah Mufridah; Heris Hendriana; Tuti Alawiyah (IKIP Siliwangi, 2021)
The purpose of this study was to determine that students' positive learning attitudes and habits can have a strong motivation or interest in learning, good study habits, positive attitudes towards subject matter, intelligence, and not easily frustrated in the face of failure. Subjects in the study were 10 students who had low positive attitudes and learning habits. The data in this study were obtained through interviews and observations about students' positive attitudes. The approach used is a quantitative approach. The method used in this research is descriptive qualitative method. The conclusion in this study is that students who have positive attitudes and learning habits will show behavior in learning activities effectively and efficiently, both in planning learning activities and participating in learning activities, understanding and mastery of subject matter, and preparing to take tests or exams.Keywords: Positive Learning Attitude, students